Epidemiological and clinical spectrum of dengue fever at tertiary care hospital in Chitwan: a hospital based study - Shrestha, Bidhan; Shrestha, Rakshya; Sedhain, Arun; Shrestha, Sabita; Dhital, Bishnu Mani; Shrestha, Suresh; Tiwari, Rituraj (Journal of Chitwan Medical College, 2020)
Background: Dengue fever is one of the most common tropical diseases caused by an arbovirus. This virus is a member of genus Flavivirus and flaviviradae family, is transmitted by bite of Aedes aegypti mosquito. Its outbreak is being reported from different parts of the world including Nepal. This disease is prevalent throughout Nepal mostly in terai regions. The aim was to study the epidemiological and clinical spectrum of dengue fever at tertiary care hospital in Chitwan. Methods: This study was a hospital based prospective study where a total of 241 patients diagnosed with dengue fever were assessed. This study was carried out from September 2019 to February 2020. Data was entered on predesigned proforma and analyzed by using SPSS version 16.0. Mean and standard deviations was calculated for continuous variables and frequencies for categorical variables. Results: More than half (56%) of the dengue patients belonged to the age group of 25-44 years. Out of 241 patients, 61.4% were males. Apart from fever the other common symptoms were retroorbital pain/headache comprising around 80% of patients. The mean duration of hospital stay in our study was 3.86 days. Approximately 72% (173) patients had leucopenia and 8.7% (21) had severe thrombocytopenia(<50000/cumm). NS1Ag positive were in 84% of total patients. Conclusions: Dengue fever is one of the dreadful diseases in tropical and hilly areas of Nepal. With the help of public health authorities, educating public about vector control and immediate medical attention may help in curbing this deadly disease.